Normative Criticism of Article 115 of the KHI on Divorce Before A Judge From A Classical Fiqh Perspective - Ahmad Fizal; Anwar Anwar; Hasanuddin Hasanuddin; Khairani Khairani; Abdul Manan (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2026)
This study aims to analyze and critique Article 115 of the Compilation of Islamic Law (KHI) concerning divorce before a judge and to examine its compatibility with the principles of classical fiqh. This research employs a descriptive qualitative design based on bibliographic and documentary sources, using a normative juridical and comparative approach. The results of the study indicate that classical fiqh positions divorce as the absolute authority of the legitimate husband without the need for judicial intervention, while the KHI limits this practice by transforming it into a judicial process for the protection of the wife and legal certainty. As a solution, this study proposes a compromise model. If Article 115 of the Compilation of Islamic Law (KHI) is to be retained, it should be reviewed to ensure its consistency with the principles of classical fiqh. Harmonization can be achieved by combining material and formal validity. The pillars and conditions of divorce still refer to the provisions of classical fiqh, but in positive law, the vow of divorce must absolutely be pronounced in a court hearing as a formal requirement for it to have binding legal force and consequences. This is crucial to prevent legal dualism and protect the civil rights of the wife after divorce. Penelitian ini bertujuan untuk menganalisa dan mengkritisi Pasal 115 Kompilasi Hukum Islam (KHI) tentang talak di depan hakim, serta meninjau kesesuaiannya dengan paradigma fikih klasik. Penelitian ini menggunakan desain penelitian kualitatif deskriptif yang didasarkan pada sumber-sumber kepustakaan dan dokumen, dengan menggunakan pendekatan yuridis normatif dan komparatif. Hasil kajian menunjukkan bahwa fikih klasik memposisikan talak sebagai otoritas mutlak suami yang sah tanpa perlu intervensi peradilan, sementara KHI membatasi praktik ini dengan mentransformasikannya ke dalam proses yudisial demi perlindungan istri dan kepastian hukum. Sebagai solusi, penelitian ini menawarkan model kompromi. Apabila Pasal 115 Kompilasi Hukum Islam (KHI) tetap dipertahankan, ketentuan tersebut perlu dikaji ulang agar tidak bertentangan dengan ketentuan fikih klasik. Harmonisasi dapat diwujudkan dengan memadukan keabsahan materiil dan formil. Rukun dan syarat talak tetap merujuk pada ketentuan fikih klasik, namun dalam perspektif hukum positif, ikrar talak wajib diucapkan di hadapan sidang pengadilan sebagai syarat formil agar memiliki kekuatan hukum dan akibat hukum yang mengikat. Ketentuan ini sangat penting untuk mencegah terjadinya dualisme hukum sekaligus memberikan perlindungan terhadap hak-hak keperdataan istri setelah perceraian.